Keterlibatan Penonton Pada Konten Ritual Di Youtube Awi Bali Channel (Analisis Evaluatif) - Artadi, Kadek; Putu Suardana, I Ketut (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2025)
This research analyzes audience involvement in ritual content on the YouTube Awi Bali Channel as a medium for preserving Hindu traditions in facing the challenges of globalization. This research uses descriptive quantitative methods with statistical analysis on 62 videos. This research evaluates engagement indicators in the form of number of views, likes and comments. The results show an average view of 2,545 per video with a fairly high level of likes of 20.19 but low comments of 1.68. This indicates the tendency of viewers to be passive consumers. External factors, such as thumbnail design, production quality, and publication time, are more significant than video length or ritual type. Pitra Yajna content had the highest engagement, confirming cultural relevance as a key factor. This research concludes that optimizing visual elements, theme relevance, and publication strategies can increase engagement, thereby strengthening YouTube's role in preserving Hindu traditions through digital platforms.